Productivity Dynamics: The Role of Competition in a Service Industry - Thomas Breda; Alex Bryson; John Forth (Institute of Labor Economics (IZA), 2019)
Using panel data for nearly all service providers in a single industry sector, we examine productivity responses to changes in competition in the United States. The sector offers workplace employee representation through trade union branches which compete with one another for union members whose subscriptions they depend on to cover costs. As such, they have an interest in maximising productivity. Ours is the first study to measure service industry productivity using both price and quantity metrics. Consistent with manufacturing studies, we find market entrants have lower prices and higher Total Factor Productivity (TFP) than incumbents. Increased competition from new entrants leads incumbents to reduce the price of union membership; exit rates then rise among incumbents with the lowest prices who are constrained in adjusting their prices downwards. Those with higher TFP have higher survival probabilities. However, increased competition does not induce incumbents to raise their TFP. These findings are consistent with a market in which incumbents learn about market conditions but face high switching costs limiting their ability to invest in the new techniques that underpin the higher TFP of new entrants.
Keywords: J5; L1; L2; L3; 330; competition; productivity; TFP; trade unions; survival